2006
DOI: 10.1007/s11604-006-0068-4
|View full text |Cite
|
Sign up to set email alerts
|

Brown tumor with fluid-fluid levels in a patient with primary hyperparathyroidism: radiological findings

Abstract: We report a case of a brown tumor with fluid-fluid levels in a patient with primary hyperparathyroidism. A 19-year-old woman presented with a 3-month history of pain in the left pubic region. The laboratory data showed elevated serum calcium and intact parathyroid hormone, confirming the diagnosis of primary hyperparathyroidism. Plain radiography and computed tomography (CT) showed an expansile lytic lesion of the superior ramus of the left pubis. The cortex was thinned. On magnetic resonance (MR) images, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
74
0
11

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(87 citation statements)
references
References 17 publications
2
74
0
11
Order By: Relevance
“…There is limited discussion of this MRI finding with brown tumors in the literature. Erem et al [11] and Takeshita et al [12] reported a brown bone tumor that on MRI was seen as an expansive mass lesion with heterogeneous hyperintensity on T2-WI in the sphenoid sinus, but without hemosiderin deposits. Accordingly, the present report is most likely the first to document MRI findings in the ribs.…”
Section: Discussionmentioning
confidence: 99%
“…There is limited discussion of this MRI finding with brown tumors in the literature. Erem et al [11] and Takeshita et al [12] reported a brown bone tumor that on MRI was seen as an expansive mass lesion with heterogeneous hyperintensity on T2-WI in the sphenoid sinus, but without hemosiderin deposits. Accordingly, the present report is most likely the first to document MRI findings in the ribs.…”
Section: Discussionmentioning
confidence: 99%
“…Radiográficamente estos tumores se presentan como lesiones líticas uni o multiloculares bien definidas con escasa formación ósea 26,27 . En la Resonancia Magnética nuclear estas lesiones son hipointensas en la secuencia T1 y de densidad mixta en la secuencia T2, esto debido a la susceptibilidad magnética de la hemosiderina, la matriz osteoide y aire 27,28 .…”
Section: Figura 5 Resección Multiestructural De Tumor Paratiroideo Yunclassified
“…Although Zhao and coworkers reported that synthetic polyphosphoesters and polyphosphoesters are enzymatically degradable (Zhao et al, 2003), the process was not described in detail. The concentration of ALP for the degradation study was adjusted to 72.5 and 220 U/L, which is the concentration in healthy adults and children, respectively (Takeshita et al, 2004;Rafan et al, 2000). Figure 6 is an enzymatic degradation profile of G1A hydrogels by changing the concentration of ALP.…”
Section: Polyphosphoester Macrocrosslinkersmentioning
confidence: 99%